2019
DOI: 10.1590/1982-0216/20192115318
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of otological symptoms and parafunctional habits in patients with temporomandibular dysfunction

Abstract: Objective: to verify the relationship between otological symptoms and parafunctional habits in individuals with temporomandibular joint dysfunction. Methods: evaluations were based on the clinical records of 768 patients treated at a temporomandibular joint diagnostic center from 2010 to 2016. The inclusion criteria were completely filled out charts of adult patients (> 18 years of age) and the final sample comprised 516 clinical records. The presence/absence of parafunctional habits and otological symptom… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
3
2

Year Published

2019
2019
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 19 publications
0
3
2
Order By: Relevance
“…Parafunctional habits have been widely recognized as etiological factors for the development of TMD [3,4]; this study confirmed the high prevalence of bruxism, clenching, nail-biting, sleeping prone, chewing gum, and talking for a long time among patients with TMD. However, unlike previously described results [13,23], the results of this study suggest that parafunctional habits do not directly imply a higher risk of new-onset tinnitus in patients with TMD.…”
Section: Discussioncontrasting
confidence: 99%
See 1 more Smart Citation
“…Parafunctional habits have been widely recognized as etiological factors for the development of TMD [3,4]; this study confirmed the high prevalence of bruxism, clenching, nail-biting, sleeping prone, chewing gum, and talking for a long time among patients with TMD. However, unlike previously described results [13,23], the results of this study suggest that parafunctional habits do not directly imply a higher risk of new-onset tinnitus in patients with TMD.…”
Section: Discussioncontrasting
confidence: 99%
“…Unlike previous studies [12,13], aural fullness was the leading otological symptom in patients with TMD and it was reported by one third of the subjects. The relationship between TMD and aural fullness is still unclear, but it might be explained by the pathological hyperactivity of the masticatory muscles and the consequent excessive tonic contraction of the tensor tympani muscle, resulting in Eustachian Tube dysfunction [14].…”
Section: Discussioncontrasting
confidence: 82%
“…It generates an increase in public costs, in demand at the secondary level, and in a worsening of the patient's clinical condition. However, a study conducted in the city of Curitiba Leao 23 found 494 (95.7%) patients that reported at least one para functional habit, related to otological symptoms 393 (76,16%) patients reported having at least one symptom, of which 138 (26,74%) with occurrence of tinnitus. This situation is contrary to the foundations of PHC which seek full and resolute attention to the patient.…”
Section: Discussionmentioning
confidence: 98%
“…Due to the multifactorial aspect of TMD, 30 it is difficult to identify the main cause for these symptoms, which may be associated with middle and inner ear dysfunctions, as well as functional disorders of the mastication organ. 18 Therefore, a multidisciplinary approach to the diagnosis and treatment of this condition is crucial.…”
Section: Discussionmentioning
confidence: 99%